PENGARUH KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEPEMILIKAN INSTITUSIONAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2014-2016 - Rawiyatul Hosnia; Roni Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACK This study aims to determine the partial variables dividend policy, investment decisions, funding decisions, institutional ownership and liquidity to corporate value. To measure dividend policy variable using dividend pauout ratio, investment decision using price earning ratio, funding decision using debt to equity ratio, institutional ownership using share of total shares owned by institution with total shares in circulation, likuitas using current rati, and company value using price book value. The population of this study is food and beverage companies listed on the stock exchanges indonesi period 2014-2016 amounted to 14 companies. The sample of this research using purposive sampling method amounted to 12 companies. The method used is multiple linear regression. The results of this study indicate that partially dividend policy has a significant positive effect, investment decisions have a significant positive effect, funding decisions have a non-significant positive effect, institutional ownership has no significant positive effect and liquidity has a significant positive effect on the value of the company on the IDX Keywords: Dividend Policy, Investment Decision, Funding Management, Institutional Status, Liquidity And Corporate Value.